2019
DOI: 10.3390/molecules24193417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anticancer Activity and HPLC-DAD Determination of Selected Isoquinoline Alkaloids from Thalictrum foetidum, Berberis sp. and Chelidonium majus Extracts

Abstract: Background: Plants are an important origin of natural substances that the raw material for various pharmaceutical and therapeutic applications due to the presence of phytochemicals, such as alkaloids. Alkaloids, which are found in different plant species, possess numerous biological activities. Some alkaloids have strong cytotoxic effects on various cancer cells. The search for new drugs to treat various cancers is one of the most important challenges of modern scientific research. Objective: This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Our data provide additional evidence that some alkaloids, such as chelerythrine, sanguinarine, and berberine, are more important in causing apoptosis or stopping the proliferation of cancer cells. Unlike the previously mentioned alkaloids, chelidonine is a weak DNA intercalating agent and does not cause lethal mutations or DNA damage [ 1 , 33 ]. This relationship is very well demonstrated in the study [ 33 ], where all these substances were tested on different cancer cells and chelerythrine, sanguinarine, and berberine showed significantly higher cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Our data provide additional evidence that some alkaloids, such as chelerythrine, sanguinarine, and berberine, are more important in causing apoptosis or stopping the proliferation of cancer cells. Unlike the previously mentioned alkaloids, chelidonine is a weak DNA intercalating agent and does not cause lethal mutations or DNA damage [ 1 , 33 ]. This relationship is very well demonstrated in the study [ 33 ], where all these substances were tested on different cancer cells and chelerythrine, sanguinarine, and berberine showed significantly higher cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In some papers, the authors have only shown chromatograms and used retention times as the main chromatographic parameter. For instance, Petruczynik et al [31] described an efficient chromatographic system to separate protopine, chelidonine, berberine, sanguinarine, and chelerythrine in a C. majus extract for 45 min on an RP-8 spherical filling with a mobile phase containing 28% acetonitrile, water and 0.04 M/L, 1-butyl-3-methylimidazolium tetrafluoroborate. Kursinszki et al [30] separated protopine, chelidonine, coptisine, berberine, and sanguinarine for 34 min on an RP-18 column with the use of a mobile phase composed of acetonitrile–methanol–30 mM ammonium formate 14.7:18:67.3 (v/v/v); however, chelerythrine, which has the strongest interaction with the stationary phase, was not included to the study.…”
Section: Resultsmentioning
confidence: 99%
“…The developed UPLC-MS/MS was used for the subsequent quantification of all Gelsemium alkaloids, which has a faster analysis time than traditional HPLC [ 35 , 36 ] or LC-MS [ 37 39 ] and greatly enhances the signal intensity. It only takes five minutes to analyze a plasma sample, which can save significant time when analyzing hundreds of samples.…”
Section: Discussionmentioning
confidence: 99%